Surgical Management Of Liver Metastases From Uveal Melanoma - Ulaș Sözener; Tevfik Eker; Sadık Ersöz (Ankara Üniversitesi Tıp Fakültesi Mecmuas)

(untitled)
Melanomas are malignant neoplasms of melanocytes developing predominantly in the skin, but occasionally arising from eyes, mucous membranes, and the central nervous system. Uveal melanoma is the most common primary intraocular malignancy in adults. The most common site of metastasis for uveal melanoma is the liver. We report the case of a 51-year-old woman with liver metastasis from choroidal melanoma and our surgical treatment.